Linkage disequilibrium mapping of a type 1 diabetes susceptibility gene (IDDM7) to chromosome 2q31-q33. - Copeman, J; Cucca, F; Hearne, C; Cornall, R; Reed, P; Rønningen, K; Undlien, D; Nisticò, L; Buzzetti, R; Tosi, R (1995)
The role of human chromosome 2 in type 1 diabetes was evaluated by analysing linkage and linkage disequilibrium at 21 microsatellite marker loci, using 348 affected sibpair families and 107 simplex families. The microsatellite D2S152 was linked to, and associated with, disease in families from three different populations. Our evidence localizes a new diabetes susceptibility gene, IDDM7, to within two centiMorgans of D2S152. This places it in a region of chromosome 2q that shows conserved synteny with the region of mouse chromosome 1 containing the murine type 1 diabetes gene, Idd5. These results demonstrate the utility of polymorphic microsatellites for linkage disequilibrium mapping of genes for complex diseases.